2018
DOI: 10.1093/cvr/cvy128
|View full text |Cite|
|
Sign up to set email alerts
|

PCSK9 expression in the ischaemic heart and its relationship to infarct size, cardiac function, and development of autophagy

Abstract: PCSK9 is up-regulated in the ischaemic hearts and determines development of infarct size, cardiac function, and autophagy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
112
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(120 citation statements)
references
References 39 publications
7
112
0
1
Order By: Relevance
“…15 Moreover, Ding et al reported that PCSK9 inhibition in mice by chemical inhibitors or gene deletion results in a significant improvement in infarct size and cardiac function, with a significant decrease in autophagy activity. 3 In view of the available data, and accordingly to our results, we hypothesize that, in patients with STEMI, treatment with PCSK9 inhibitors might play a role by limiting adverse left ventricular postmyocardial infarction remodelling beyond its beneficial effects on the lipid profile and plaque stabilization. These myocardial effects could also explain part of the beneficial clinical effects found with PCSK9 inhibitors.…”
Section: Proprotein Convertase Subtilisin/kexin Type 9 As a Potentialsupporting
confidence: 73%
See 2 more Smart Citations
“…15 Moreover, Ding et al reported that PCSK9 inhibition in mice by chemical inhibitors or gene deletion results in a significant improvement in infarct size and cardiac function, with a significant decrease in autophagy activity. 3 In view of the available data, and accordingly to our results, we hypothesize that, in patients with STEMI, treatment with PCSK9 inhibitors might play a role by limiting adverse left ventricular postmyocardial infarction remodelling beyond its beneficial effects on the lipid profile and plaque stabilization. These myocardial effects could also explain part of the beneficial clinical effects found with PCSK9 inhibitors.…”
Section: Proprotein Convertase Subtilisin/kexin Type 9 As a Potentialsupporting
confidence: 73%
“…Inhibition of proprotein convertase subtilisin/kexin type 9 (PCSK9) has emerged as a novel and effective therapy for treating hypercholesterolemia . Some experimental evidence suggests that PCSK9 is up‐regulated in vascular smooth muscle cells and ischemic hearts, playing a potential pathogenic role in infarct size, cardiac function, and autophagy . In addition, recent clinical evidence indicates that plasma PCSK9 is positively related to a higher risk of adverse events in a large cohort of patients with acute heart failure with predominantly left ventricular systolic dysfunction and ischemic heart disease …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the cardioprotective effects of PCSK9 inhibitor had been reported in mice, this was done in chronic myocardial infarction model. Moreover, findings from that study had a limitation for its clinical application to acute myocardial infarction cases since PCSK9 inhibitor was given only prior to myocardial ischaemia. In our study, acute administration of PCSK9 inhibitor was done in an acute myocardial ischaemia/reperfusion injury model in rats.…”
Section: Introductionmentioning
confidence: 99%
“…A proprotein convertase subtilisin/kexin 9 (PCSK9) inhibitor as well as high doses of atorvastatin lowers the ratio between phosphorylated and total Drp‐1, a key factor in mitochondrial fission, whereas only the PCSK9 inhibitor restores mitochondrial ROS levels in insulin‐resistant, dyslipidaemic rats . Expression of PCSK9 is increased in the viable reperfused myocardium and its pharmacological inhibition can reduce infarct size, possible through autophagy, in the in vivo mouse model of myocardial infarction . Paradoxically, although some statins such as pravastatin seem to facilitate MPTP opening, atorvastatin reduces infarct size in the isolated mouse‐perfused hearts by activating the Akt‐eNOS pathway, suggesting that MTPT modulation may vary between statins.…”
Section: Challenges In Translating Mitoprotection Into the Clinical Smentioning
confidence: 99%